Model Behavior Contract Melalui Layanan Penguasaan Konten Untuk Mereduksi Addiction Smartphone Use - Wahyu Almizri (Fakultas Dakwah Intitut Agama Islam Riyadlotul Mujahidin Ngabar (IAIRM) Ponorogo, 2022)
Advances in technology, information and communication are increasingly felt in the millennial era. Technology in the field of communication that is the result of the times is the smartphone. Indonesian people have the potential to be addicted to smartphones, especially among teenagers. Addiction to smartphones certainly has many negative impacts, one of which is that people become apathetic, people become less concerned about their surroundings because they are more focused on smartphones. The purpose of this study is to obtain an analysis of the conditions in reducing smartphone addiction in educational activities. Guidance and counseling teachers or counselors (BK/Counselors) have a role to provide guidance and counseling services. One of the services that can be provided to reduce smartphones is content mastery services with a behavioral contract approach model. The research findings reveal that in reducing smartphone addiction behavior through the behavior contract model, individuals can control themselves more and be wise in using their smartphones. Keywords: Guidance and Counseling, behavior contracts, smartphone addiction